When the party is over: developments in Sochi and Russia after the Olympics 2014 - Petersson, B.; Vamling, K.; Yatsyk, A. (Sport in Society: Cultures, Commerce, Media, Politics, 2017)
The 2014 Winter Olympic Games in Sochi, Russia, were during the preparations and run-up phase intensely followed by the global community and were generally associated with a vast array of problems: political, democratic, economic, ecological and security-related. When the hosting of a mega-event such as the Olympic Games has been awarded to a site in an authoritarian state, the global community has moral responsibilities to live up to. There is a need and an obligation to raise one`s voice and criticize where criticism is due also after the Games are concluded. For Sochi, as for sites of all major sports events, continued critical attention is therefore warranted also after the competitions. It is essential to try to gauge the extent to which predicted problems materialized, what happened afterwards and what have been the more long-term consequences and local effects. This is the general perspective that brought the authors of this volume together.